A Prospective Study Evaluating Gender Differences of Serious Outcomes through Difficult Airway Physiological Score (DAPS) in the Emergency Department - Shahan Waheed; Rida Jawed; Ahmed Raheem; Asad Iqbal Mian (Critical Care Research and Practice)
Introduction. Gender variation in critically ill adults after resuscitation is reported in many studies. However, this variation is not well established when evaluating the physiological instability in this population. This study aimed to prospectively evaluate the gender variation in serious outcomes by the difficult airway physiological score (DAPS) among critically ill patients requiring endotracheal intubation (ETI). Methods. This is a cohort study conducted from August 2021 to December 2022 in the emergency department of Aga Khan University. The prospective validity of the difficult airway physiological score was derived using retrospective data and includes 12 variables: sex, age, time of intubation, hypotension, respiratory distress, vomiting, shock index >0.9, pH < 7.3, fever, anticipated decline, Glasgow Coma Scale (GCS) < 15, and agitation. The serious outcomes were cardiac arrest, mortality (within 1 hour after intubation in emergency), hypotension (systolic blood pressure <90 mmHg), and oxygen desaturation (SpO2 < 92%). The difference between males and females was assessed using the chi-square test, and the association of gender and serious outcomes was explored using Cox and logistic regression analysis. ROC curve analysis and area under the curve assessed score validity separately in males and females with serious outcomes. Results. We enrolled 326 patients with a mean age of 50.3 (±17.8), with 123 (33.7%) females and 203 (62.2%) males. 198 (60.7%) patients were >45 years old, of which 136 (67%) were male and 62 (50.4%) female. Cardiac arrest was observed in 56 (17.2%), with 24 (19.5%) females and 32 (15.8%) males, p value 0.348. Hypotension after intubation was observed in 132 (40.5%) patients, 56 (45.5%) females and 76 (37.4%) males, p value 0.149. Oxygen saturation (<92%) was observed in 80 (24.5%) patients, 32 (26%) females and 48 (23.6%) males, p value 0.630. In females, the DAPS of 11 had an area under the curve of 0.863 (0.74–0.91). The sensitivity of the score was 84.8%, the specificity was 71.9%, the PPV was 77.8%, and the NPV was 80.4% with an accuracy of 78.9%. In males, the DAPS score of 14 had an area under the curve of 0.892 (0.57–0.75). The sensitivity of the score was 67%, the specificity 93.8%, the PPV 92.2%, and the NPV 72.2% with an accuracy of 79.8%. Conclusions. The Difficult Airway Physiological Score (DAPS) predicts the risk of serious outcomes after intubation with high precision and reliability with different score cutoffs between the two sexes, highlighting the gender variation of a difficult airway.